History and Scope of Right of Lien in Shia’s Jurisprudence (A Comparative Perspective of Sunni Jurisprudence and Western Law) - Mohsen Jahangiri; Gholam Reza Yazdani (آموزه‌‌های فقه مدني)
The right of refraining from carrying out the commitment in order to implement the commitment of the other party, is called right of Lien. The right of Lien has been accepted by Islamic jurists for a long time. No one has doubted about its accuracy in Shia’s jurisprudence until Mohaghegh Ardabil. And after it was understood illegitimate by him and was followed by some researchers, seyyed Ameli again replied the doubts of Mohaghegh Ardabili and his followers. The origin of the right of lien should be investigated in the implicit will of the parties. Therefore, the right of line is extended not only to all contracts and transactions, but also after the dissolution of the contract.